Does multitasking in the classroom affect learning outcomes? A naturalistic study. (May 2020) - Jamet, Eric; Gonthier, Corentin; Cojean, Salomé; Colliot, Tiphaine; Erhel, Séverine
Abstract: University students often engage in multimedia (e.g., texting or social networks) and nonmultimedia (e.g., chatting with neighbors) off-task multitasking behaviors during courses. The aim of the present study was to describe these off-task multitasking behaviors and analyze their effects on learning performance in a real teaching session. More specifically, 187 students attended a cognitive psychology tutorial as usual, taking notes either on paper or on a laptop. In an effort to preserve the ecological setting, they were not informed of our research on multitasking. After 20 min, students had to report the number and duration of off-task multitasking behaviors they had engaged in and complete a learning questionnaire. Results showed that multimedia and nonmultimedia multitasking behaviors were frequent but also additive, especially among students who used a laptop. These behaviors had a negative impact on students' memorization of course content, although we found no significant effects on comprehension. Our study also showed that students who used a laptop had lower memory scores. A mediation analysis confirmed that this deleterious effect was partly attributable to multitasking. These results are discussed in terms of interference between off-task behaviors and the cognitive processes essential for learning. Highlights: We studied off-task multitasking effects on learning in a real-life teaching session. Students engaged in numerous multimedia and nonmultimedia multitasking behaviors. Multitasking behaviors had a negative impact on the memorization of lecture content. Students who used a laptop engaged in more multitasking and had lower memory scores.